Atom Economic Ruthenium‐Catalyzed Synthesis of Bulky β‐Oxo Esters. Issue 18 (25th November 2015) - Jeschke, Janine; Korb, Marcus; Rüffer, Tobias; Gäbler, Christian; Lang, Heinrich
Abstract: Ruthenium complexes with the formulae Ru(CO)2 (PR3 )2 (O2 CPh)2 [6a –h ; R= n‐ Bu, p ‐MeO‐C6 H4, p ‐Me‐C6 H4, Ph, p ‐Cl‐C6 H4, m ‐Cl‐C6 H4, p ‐CF3 ‐C6 H4, m, m′ ‐(CF3 )2 C6 H3 ] were prepared by treatment of triruthenium dodecacarbonyl [Ru3 (CO)12 ] with the respective phosphine and benzoic acid or by the conversion of Ru(CO)3 (PR3 )2 (8e –h ) with benzoic acid. During the preparation of8, ruthenium hydride complexes of type Ru(CO)(PR3 )3 (H)2 (9g, h ) could be isolated as side products. The molecular structures of the newly synthesized complexes in the solid state are discussed. Compounds6a –h were found to be highly effective catalysts in the addition of carboxylic acids to propargylic alcohols to give valuable β‐oxo esters. The catalyst screening revealed a considerably influence of the phosphine′s electronic nature on the resulting activities. The best performances were obtained with complexes6g and6h, featuring electron‐withdrawing phosphine ligands. Additionally, catalyst6g is very active in the conversion of sterically demanding substrates, leading to a broad substrate scope. The catalytic preparation of simple as well as challenging substrates succeeds with catalyst6g in yields that often exceed those of established literature systems. Furthermore, the reactions can be carried out with catalyst loadings down to 0.1 mol% and reaction temperatures down to 50 °C. Abstract :